Project-based learning: Improving students’ activity and comprehension through lesson study in senior high school - Rofieq, Ainur; Latifa, Roimil; Susetyarini, Eko; Purwatiningsih, Purwatiningsih (Jurnal Pendidikan Biologi Indonesia, 2019)
Fostering teacher’s creativity can be facilitated by conducting Lesson Study (LS) which implementing Project-Based Learning (PjBL) using designing learning resources. This descriptive qualitative research was using a model teacher who did three open classes on ‘human reproduction system’ material and targeting the twelfth grade of senior high school students in Sumberpucung Malang as the research subject. The observers comprised three teachers and three lecturers. As for reflection in every open class, four students involved as the informants. The implementation of the model was considered very effective to improve the students’ learning activities, due to several reasons, namely: (a) almost all of the students were actively get involved in the learning process; (b) there was an improvement in the number of active students; (c) the instruction was positive to uplift the quality of classroom management; (d) the students were stimulated in formulating questions and giving opinions; (e) joyful learning was created; (f) most of the students had gained prior knowledge and comprehension of the given problems and concepts before they were presenting it.